Reduced predation and energy flux in soil food webs by introduced tree species: Bottom‐up control of multitrophic biodiversity across size compartments - Lu, Jing‐Zhong; Wenglein, Ronja; Bluhm, Christian; Stuckenberg, Thalea; Potapov, Anton M.; Ammer, Christian; Scheu, Stefan (Functional ecology, 2025)
The introduction of non‐native tree species has become a global concern and may disrupt native communities and related ecosystem functions. Soil food webs regulate organic matter decomposition and nutrient cycling in forests with their feeding activities, but evaluating consequences of the introduction of tree species on soil invertebrates is challenging due to the complex trophic structure and wide range in body size of soil invertebrates. Here, we employed an energetic food web approach and estimated the energy flux in soil food webs using a four‐node model including soil meso‐ and macrofauna decomposers and predators. We examined pure and mixed stands of native European beech (Fagus sylvatica), introduced Douglas fir (Pseudotsuga menziesii) and native range‐expanding Norway spruce (Picea abies) across site conditions. Compared to native forests, introduced tree species reduced total fresh mass of macrofauna predators by 92% at sandy sites but not that of decomposers, suggesting trophic downgrading in soil food webs by Douglas fir. The energy flux in mixed forests was intermediate between respective monocultures, suggesting that tree mixtures mitigate potential negative impacts of introduced tree species on food web functioning. Across size classes, soil macrofauna responded more sensitively to changes in environmental conditions than soil mesofauna. Additionally, total energy flux positively correlated with species richness, pointing to the significance of soil biodiversity for trophic functionality. The energy flux through mesofauna outweighed that through macrofauna when considering energy loss to predators, highlighting the importance of mesofauna for decomposition processes in forest soil food webs. Overall, the study emphasizes the critical role of tree species composition, site conditions and soil biodiversity in driving energy flux through soil food webs and maintaining forest ecosystem functions. Read the free Plain Language Summary for this article on the Journal blog. Zusammenfassung Die Einführung nicht‐einheimischer Baumarten ist ein globales Problem und kann einheimische Gemeinschaften und die damit verbundene Ökosystemfunktionen beeinträchtigen. Bodennahrungsnetze regulieren den Abbau organischer Stoffe und den Nährstoffkreislauf in Wäldern, jedoch sind die Auswirkungen der Einführung von nicht‐einheimischen Baumarten auf Bodeninvertebraten aufgrund der komplexen trophischen Struktur und der großen Bandbreite an Körpergrößen von Bodeninvertebraten wenig untersucht. Wir untersuchten den Energiefluss in Bodennahrungsnetzen mit einem Vier‐Knoten‐Modell, das Bodenmeso‐ und Makrofauna‐Zersetzer sowie Bodenmeso‐ und Makrofauna‐Prädatoren umfasste. Wir analysierten reine und gemischte Bestände der einheimischen europäischen Buche (Fagus sylvatica), der eingeführten Douglasie (Pseudotsuga menziesii) und der einheimischen Fichte (Picea abies) unter verschiedenen Standortbedingungen. Im Vergleich zu einheimischen Wäldern reduzierte die Douglasie die Gesamtmasse der Makrofauna‐Prädatoren auf sandigen Böden um 92%, jedoch nicht die der Zersetzer, was auf ein trophisches “downgrading” der Bodennahrungsnetze hindeutet. Der Energiefluss in Mischwäldern lag zwischen den jeweiligen Monokulturen, was darauf hindeutet, dass Baummischungen potenzielle negative Auswirkungen eingeführter Baumarten auf die Funktionsweise von Nahrungsnetzen abmildern. Über alle Größenklassen hinweg reagierte die Bodenmakrofauna empfindlicher auf Umweltveränderungen als die Bodenmesofauna. Zudem korrelierte der Gesamtenergiefluss positiv mit der Artenvielfalt, was die Bedeutung der Bodenbiodiversität für die trophische Funktionalität unterstreicht. Trotz der geringeren Gesamtmasse überwog der Energiefluss durch die Mesofauna den durch die Makrofauna, wenn der Energieverlust durch Prädation berücksichtigt wurde, was die Bedeutung der Mesofauna für Zersetzungsprozesse in Bodennahrungsnetzen hervorhebt. Insgesamt betont die Studie die entscheidende Rolle der Baumarten‐Zusammensetzung, der Standortbedingungen und der Bodenbiodiversität für den Energiefluss in Bodennahrungsnetzen und die Erhaltung der Waldökosystemfunktionen. Read the free Plain Language Summary for this article on the Journal blog.